Phytochemical screening of extracts from Spiranthera odoratissima A. St.-Hil. (Rutaceae) leaves and their in vitro antioxidant and anti-Listeria monocytogenes activities - Souza, Amanda de Oliveira; Bessa, Dâmaris Hadassa Rangel Fonseca; Fernandes, Cassia Cristina; Pereira, Paulo Sérgio; Martins, Carlos Henrique Gomes; Miranda, Mayker Lazaro Dantas (Acta Scientiarum. Biological Sciences, 2020)
Spiranthera odoratissima A. St.-Hil (Rutaceae), a shrub whose common name is manacá do Cerrado in Brazilian Portuguese, is about 1-m high and has been used by folk medicine to treat stomachache, kidney and liver infections, headache, rheumatism and as a blood purifier. This study aimed at preparing hexane, ethyl acetate, methanolic, hydroethanolic and aqueous extracts from S. odoratissima leaves, at carrying out preliminary phytochemical screening and at evaluating their in vitro antioxidant and anti-Listeria monocytogenes activities. Antioxidant activity was evaluated by the DPPH (2,2-diphenyl-1-picrylhydrazyl), ABTS (2,2-azinobis-3-ethybenzothiazoline-6-sulfonate) and FRAP (ferric reducing antioxidant power) methods. Antibacterial activity was investigated against L. monocytogenes and Minimum Inhibitory Concentration (MIC) values of plant extracts were calculated by the broth microdilution method with the use of 96-well plates. In aqueous, methanolic, hydroethanolic, ethyl acetate and hexane extracts from S. odoratissima leaves, the following classes of compounds were investigated: organic acids, reducing sugars, flavonoids, saponin compounds, coumarin compounds, phenolics, tannins, purine compounds, catechins, flavonol derivatives, sesquiterpene lactones and anthraquinones. All plant extracts, except the hexane one, exhibited high antioxidant activity. Regarding antibacterial activity, the most polar extracts showed high activity against L. monocytogenes; their MIC values ranged between 12.5 and 62.5 µg mL-1, while the hexane one exhibited low activity (MIC = 1000 µg mL-1). In short, extracts from S. odoratissima leaves may be considered promising sources of secondary metabolites with relevant antioxidant and antibacterial activities.